PENDAMPINGAN MANAJEMEN KEUANGAN BERBASIS SISTEM INFORMASI AKUNTANSI KOPERASI WANITA DEWI KUNTI - Ruscitasari, Zulfatun; Millaty, Marosimy (Universitas Borneo Tarakan, 2022)
Financial management is one of the important aspects in supporting the performance of co-operatives. Savings and Loans Co-operative (KSP) is one of the financial institutions favored by the public because it can provide access to capital with less complicated administration. One of the Savings and Loans Co-operatives in the Special Region of Yogyakarta is the Dewi Kunti Women's Cooperative which is located in Kaluhan Panggungharjo, Bantul. Currently, the Dewi Kunti Cooperative has problems in financial management, namely the limited ability of the co-operative management to keep records neatly, the emersion of bad loans from the members and also not having updated data on cooperative members. In addition, several credit loans made by members were experiencing bottlenecks and the Dewi Kunti Women's Co-operative member database had not been updated. The output of this research is an increase in the ability of the management in conducting cooperative financial administration and compiling IT-based financial reports. In addition, currently the co-operative has the most updated database of cooperative members.